Analyzing Muscle Damage (CK-MM) and Recovery of Muscle Strength between Non-Professional and Professional Basketball Athletes - Eby Mahbubi; Lilik Herawati; Damayanti Tinduh; Irfianayah Irwadi; Raden Argarini; Gadis Meinar Sari; Ulul Azmy; Nur Ashikin Mohd Zaki (Physical Education Theory and Methodology, 2025)
Background. Basketball is considered to be one of the most popular sports. Besides recreational training sessions, basketball lovers as non-professional athletes often perform competitions like basketball athletes, characterized by high intensity. However, the biological changing is limited.